NIAT MELAKUKAN PERKAWINAN DINI : TINJAUAN PLANNED BEHAVIOR THEORY - Juniata, Stacia (University of Surabaya, 2016)
Early marriage is a marriage conducted by teenagers who are still in the age of puberty. Intention to marriage can be measured with planned behavior theory. Planned Behavior explained that intention to perform a behavior is based on three aspect. The three aspect are attitude, subjective norms, and perceived behavioral control. The aim of this study is to know the description of early marriage intention among girls that live in Genitri village and to prevent early marriage in Genitri villlage. The subjects of this research were female adolescents aged 15-19 years that lived in Genitri village. The quistionaire contain open question and close question about application planned behavior theory (Susanto,2012). Data will be analyzed using spearman non-parametric correlation test and stepwise regression test. The result showed there were correlation between early marriage intention with attitude, subjective norms, and perceived behavioral control when analyzed together (r = 0.87, sig = 0.000), but when analyzed separated there were no correlation between intention of early marriage with subjective norms. Aspect perceived behavioral control have the most contribution in determining intention of early marriage.